Effect of nitrogen fertilizers on productivity of Urtica pilulifera plant - HEND E. WAHBA; HEMAIA M. MOTAWE; ABBER Y. IBRAHIM (Nusantara Bioscience, 2014)
Abstract. Wahba HE, Motawe HM, Ibrahim AY. 2014. Effect of nitrogen fertilizers on productivity of Urtica pilulifera plant. Nusantara Bioscience 6: 49-56. Urtica pilulifera L. have been known for a long time as a medicinal plant for treatments of many diseases, but its agricultural studies and chemical composition did not have enough researches. Two field experiments were carried out at the experimental farm of Faculty of Agriculture, Cairo University during two successive seasons 2009 and 2010, to study the effect of nitrogen dressing application (Urea, ammonium nitrate and ammonium sulfate) at different doses (0, 20, 40 and 60 N units/fed.) on growth, yield parameters and chemical composition of Urtica pilulifera plants. The results showed that the application of all nitrogen forms significantly increased the determined parameters as compared to untreated plants and the best treatment was ammonium sulfate at 60 N unit to increase quantitative and qualitative plant production.